2019
DOI: 10.3390/polym11081321
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of SBR-Modified Cementitious Mixtures for Use as 3D Additive Construction Materials

Abstract: The primary purpose of this study was to investigate the feasibility of applying polymeric cementitious materials to three-dimensional additive construction (3DAC). Specifically, styrene–butadiene rubber (SBR) latex was employed as an admixture to produce SBR-modified cementitious mixtures, and their fresh properties were experimentally investigated to determine the feasibility of their use in the 3DAC process. The SBR/cement ratio was controlled based on four main materials (i.e., cement, sand, silica fume, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
1
Order By: Relevance
“…al. [13]. However, we still do not know yet whether the mixtures that can be utilized for 3DAC are stable enough to maintain their original dimensions after the mixtures have been printed (i.e., it is exposed to ambient temperature and humidity).…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [13]. However, we still do not know yet whether the mixtures that can be utilized for 3DAC are stable enough to maintain their original dimensions after the mixtures have been printed (i.e., it is exposed to ambient temperature and humidity).…”
Section: Research Objectivesmentioning
confidence: 99%
“…SBR latex was added according to the SBR/cement ratios (i.e., 0, 0.05, 0.10, 0.15, and 0.20). The amount of water used was determined based on a water/cement ratio that could maintain a flow of 70% ± 1% for each mixture because the flow of 70% ± 1% was determined by Kim et al [13] as the optimal flow of SBR-modified cementitious mixtures to apply 3DAC. Table 8 shows the mixture proportions identified for these conditions.…”
Section: Mixture Proportionsmentioning
confidence: 99%
“…Since vinyl pyridine latex is poorly immersed in fabrics, its main engineering application is the immersion of tires in the textile industry [18]. In civil engineering field, SBR is utilized as a substitute of cement to boost the hardened properties of concrete [19]. The research outcome was observed that the effect of addition SBR on the characteristics strength concrete.…”
Section: Introductionmentioning
confidence: 99%
“…SBR, çeşitli malzemelerle başarılı bir şekilde birleştirilebilen, bütadien, stiren ve su içeren geniş dağılımlı bir polimerdir [17][18]. İnşaat mühendisliği alanında SBR, betonun sertleşmiş özelliklerini artırmak için çimentonun bir ilavesi olarak kullanılmaktadır [19]. Araştırma sonucunda SBR ilavesinin betonun dayanım özelliklerine etkisi olduğu görülmüştür.…”
Section: Introductionunclassified